Pengaruh Insecure / Kepercayaan Diri Terhadap Motivasi Belajar Siswa Kelas X Putri SMA MTA Surakarta - Bilqiis Al-Ghaadah Santifa (Pusat Riset dan Inovasi Nasional, 2024)
The state of insecurity is an emotional problem. Insecure feels tense, anxious, and experiences conflict along with various consequences. A person's motivation causes feelings of insecurity in studying English. Insecurity itself can appear in various aspects of life, for example in work, social relationships, and even physical appearance.. This feeling of insecurity can hinder emotional well-being and reduce a person's quality of life.. On average, women experience insecurity. , especially in Indonesia..There are several reasons why Indonesian women feel insecure (not confident)..One of the main factors is due to their physical shape. The aim of this research is to determine the effect of self-confidence on the learning motivation of class X female students at SMA MTA Surakarta. The method in this research uses a quantitative descriptive method to analyze data about what factors cause students' motivation and feelings of insecurity. The subjects in this research were female class X students at SMA MTA Surakarta. The results of this research are the lack of a strong and significant influence between Insecurity and learning motivation.